MR susceptibility imaging for detection of tumor-associated macrophages in glioblastoma - Nazem, Amir; Guiry, Samantha C.; Pourfathi, Mehrdad; Ware, Jeffrey B.; Anderson, Hannah; Iyer, Srikant Kamesh; Moon, Brianna F.; Fan, Yi; Witschey, Walter R.; Rizi, Rahim; Bagley, Stephen J.; Desai, Arati; et al. (Journal of neuro-oncology, 2022)
Purpose Tumor-associated macrophages (TAMs) are a key component of glioblastoma (GBM) microenvironment. Considering the differential role of different TAM phenotypes in iron metabolism with the M1 phenotype storing intracellular iron, and M2 phenotype releasing iron in the tumor microenvironment, we investigated MRI to quantify iron as an imaging biomarker for TAMs in GBM patients. Methods 21 adult patients with GBM underwent a 3D single echo gradient echo MRI sequence and quantitative susceptibility maps were generated. In 3 subjects, ex vivo imaging of surgical specimens was performed on a 9.4 Tesla MRI using 3D multi-echo GRE scans, and R2* (1/T2*) maps were generated. Each specimen was stained with hematoxylin and eosin, as well as CD68, CD86, CD206, and l -Ferritin. Results Significant positive correlation was observed between mean susceptibility for the tumor enhancing zone and the l -ferritin positivity percent (r = 0.56, p = 0.018) and the combination of tumor’s enhancing zone and necrotic core and the l -Ferritin positivity percent (r = 0.72; p = 0.001). The mean susceptibility significantly correlated with positivity percent for CD68 (ρ = 0.52, p = 0.034) and CD86 (r = 0.7 p = 0.001), but not for CD206 (ρ = 0.09; p = 0.7). There was a positive correlation between mean R2* values and CD68 positive cell counts (r = 0.6, p = 0.016). Similarly, mean R2* values significantly correlated with CD86 (r = 0.54, p = 0.03) but not with CD206 (r = 0.15, p = 0.5). Conclusions This study demonstrated the potential of MR quantitative susceptibility mapping as a non-invasive method for in vivo TAM quantification and phenotyping. Validation of these findings with large multicenter studies is needed.